Role of serotonin in the regulation of aldosterone secretion from the rat adrenal gland - Burns, Nicola Jane Tait (The University of Edinburgh, 2002)
In 1959 Rosenkrantz et al., first described the effect of the indoleamine serotonin on aldosterone secretion from the adrenal gland. To date numerous studies have reported this steroidogenic effect, describing the second messenger system utilised and in some species the receptor type involved. However the full physiological and pathophysiological role of serotonin in the control of mineralocorticoid secretion still remains to be elucidated.

Classically serotonin has always been thought to be the major indoleamine involved in the modulation of aldosterone secretion from the zona glomerulosa, a fact that has not been proven. To resolve this, numerous indoleamines, both naturally occurring and synthetic congeners, were studied in isolated rat zona glomerulosa cells for their ability to induce aldosterone secretion, as compared to serotonin. Of the compounds tested, 5-methoxytryptamine, tryptamine, N-methyltryptamine, 5-methyltryptamine, 6- methoxytryptamine and 5-hydroxytryptophan (5-HTP) stimulated, to various degrees aldosterone secretion, from the zona glomerulosa. Of those compounds tested that produced comparable stimulation of aldosterone as that produced by serotonin, cAMP output was also investigated and it was observed that all compounds stimulated cAMP output also, to varying degrees. The study allowed specific structural requirements, required for stimulation of aldosterone secretion, to be characterised, namely that the 5- hydroxyl grouping was not required for full agonist activity, but ring substitutions at other positions compromise agonist activity. The basicity of the terminal amine group is important also in receptor binding. This study will aid in the search for specific agonists and antagonists, required for the research into the serotonin receptor present within the zona glomerulosa.

Unlike the cardiovascular and CNS, where specific receptors have been identified and categorised, specific receptors within the rat zona glomerulosa for serotonin have not yet been fully characterised. The second study of this thesis aimed at characterising the receptors found within rat zona glomerulosa by utilising an array of serotonin agonists and antagonists. The antagonists ketanserin and mesulergine were found to inhibit serotonin induced aldosterone secretion, and the agonists 5-methoxytryptamine and 5- carboxamidotryptamine, produced identical stimulation of aldosterone from rat zona glomerulosa, as that produced with serotonin. This effect was also found to be affected by sodium status. These results taken together with previous studies and preliminary studies with a 5-HT7 probe in sections of rat adrenal gland would suggest the presence of a 5-HT7 receptor in rat zona glomerulosa, although the presence of other serotonin receptors can not be ruled out.

For serotonin to have a physiological role in aldosterone secretion, a local source of serotonin would be required. In consideration of this the role of the enzyme Laromatic amino acid decarboxylase (L-AAAD) in the local production of serotonin and dopamine was investigated in rat adrenal zona glomerulosa, in animals maintained on varying sodium diets. The presence of L-AAAD was located, via immunohistochemistry, in the zona glomerulosa, zona fasciculata and the medulla. Conversion of 5-HTP to serotonin and L-DOPA to dopamine was observed in capsular and medullary tissue preparations, and this was inhibited by carbidopa. 5-HTP significantly stimulated aldosterone secretion, from capsular tissue. This effect was more apparent in animals on a low salt diet and less apparent in high salt diet animals as compared to animals maintained on a normal salt diet. The opposite was true for studies with L-DOPA. The effect of sodium status would suggest that the enzyme is regulated by salt intake. No significant effect of L-DOPA and of 5-HTP on corticosterone secretion from tissue preparations was observed. The results from this study provide evidence for a role for L-AAAD in converting circulating L-DOPA and 5-HTP to dopamine and serotonin, to either inhibit or stimulate aldosterone secretion from the rat zona glomerulosa.

The role of the serotonin transporter was studied within the rat adrenal gland. The transporter molecule was visualised throughout the rat adrenal medulla via immunohistochemistry. The serotonin uptake inhibitors citalopram and desmethylimipramine (DMI) were incubated with or without serotonin in isolated rat zona glomerulosa cells and the resulting aldosterone secretion was measured. Results varied and this was thought to be due to the harsh collagenase digestion process destroying the transporter, and so whole capsular tissue was studied in a superfusion system and aldosterone secretion measured. In all cases both reuptake inhibitors increased the aldosterone output from capsular tissue. The drug of abuse methylenedioxymethamphetamine (MDMA; 'Ecstasy') was also used in this system, and this compound also caused an increase in aldosterone secretion. In Vivo studies with MDMA produced interesting results with an increase in plasma aldosterone and PRA. From this study evidence has been found for the existence of the serotonin transporter molecule within the rat adrenal gland. MDMA may induce a rise in aldosterone concentration within the plasma by a direct action on the serotonin transporter within the adrenal gland.

This thesis has provided strong evidence for a role of serotonin in the control of aldosterone secretion in the rat. Serotonin can be produced locally within the adrenal cortex and induce aldosterone secretion, and this action may be switched on in cases of low sodium status. Further studies are required to fully characterise the serotonin receptor, to elucidate a role for the transporter within the gland and to understand more fully the importance of serotonin and indeed dopamine, in the physiology and pathophysiology of the adrenal cortex.